Sosialisasi Sadar Wisata dan Sapta Pesona Masyarakat Pantai KSS Desa Sukawali - Setiawati, Yuli (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Sukawali Village is one of the villages located in Pakuhaji District, Tangerang Regency, which has tourism potential in the form of beach tourism, namely KSS Beach and mangrove ecotourism. In 2023, the Indonesian Navy established the Kampung Bahari Nusantara (KBN) to manage 5 (five) pillars for the Sukawali Village community, including the Pillars of Education, Resilience, Economy, Health, and Tourism. In strengthening the Tourism pillar, the implementation of community service programs regarding the understanding of Tourism Awareness and the application of the Sapta Pesona elements at the KSS Beach Tourist Attraction. Assistance is carried out through counseling activities in the form of lectures on Tourism Awareness and Sapta Pesona Socialization and continued with discussions with stakeholders and the community around KSS Beach, which resulted in a basic understanding of the KSS beach community regarding Tourism Awareness and Sapta Pesona through tests before and after the counseling was given, and the handover of the Sapta Pesona Board symbolization and trash bins for traders around KSS Beach. Furthermore, there will be monitoring of the implementation of the Sapta Pesona elements carried out by the KSS Beach community to encourage the growth and development of the KSS beach tourism industry in Sukawali Village